Prioritizing School Social Workers' Roles and Responsibilities to Combat Oppression in K-12 Schools: Perspectives from Educators with Anti-oppressive Orientations - Ashley-Marie Hanna Daftary (International Journal of School Social Work, 2020)
This study used a subset of data from a larger qualitative research study that investigated anti-oppressive practices in K-12 education. Eleven educators with anti-oppressive orientations provided insight into various ways school social workers can combat oppression in K-12 schools. A flexible coding approach was used to analyze the data. Findings suggest that school social workers should consider prioritizing the following activities to combat oppression in schools: 1) Provide leadership in social justice work and anti-oppressive practice; 2) Increase visibility and integration on campus and in the classroom; and 3) Complement student interventions with psycho-education and social-emotional support for teachers. The findings support literature that endorses the utilization of systems change strategies in addition to direct interventions. Implications for school social work practice, research, and education are discussed.
Keywords: school social work; combatting oppression; anti-oppressive practice; social justice; K-12 schools